2001
DOI: 10.1063/1.1339886
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-one- and two-dimensional transitions of gases adsorbed on nanotube bundles

Abstract: Grand canonical Monte Carlo simulations have been performed to determine the adsorption behavior of Ar and Kr atoms on the exterior surface of a rope ͑bundle͒ consisting of many carbon nanotubes. The computed adsorption isotherms reveal phase transitions associated with the successive creation of quasi-one-dimensional lines of atoms near and parallel to the intersection of two adjacent nanotubes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
80
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 28 publications
12
80
2
Order By: Relevance
“…In recent years much experimental effort has been devoted to the study of structural and thermal properties of such systems and a number of theoretical models have been advanced to predict these properties [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. However, the thermal expansion behavior of SWNT-gas impurity systems still remains obscure.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years much experimental effort has been devoted to the study of structural and thermal properties of such systems and a number of theoretical models have been advanced to predict these properties [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. However, the thermal expansion behavior of SWNT-gas impurity systems still remains obscure.…”
Section: Introductionmentioning
confidence: 99%
“…cylindrical pore with multiple layers, we assume the interlayer spacing is constant, ∆ = 0.3354 nm (Charlier and Michenaud 1993;Ge and Sattler 1993). To investigate the effects of surface strength, we choose a cylindrical pore whose surface is graphite-like but its well-depth is 60% that of graphite, i.e.…”
Section: Solid-fluid Potentialmentioning
confidence: 99%
“…Jakubek and Simard (2004) reported the formation of two condensed phases of argon adsorbed onto single-walled carbon nanotubes and found the critical pressures of the onset of the quasi-one-dimensional linear phase and the quasi-two-dimensional monolayer phase formation on the external surface at 77 K and 87.3 K, respectively. A number of workers (Gatica et al 2001(Gatica et al , 2008Gatica and Cole 2005;Urban et al 2005) have undertaken theoretical investigations of the quasi-1D and -2D phase transitions for gases adsorbed onto nanotube bundles. Recently, Wang et al (2010), using carbon nanotubes as resonators, have observed the formation of argon monolayers on the cylindrical surface and a phase transition from fluid to solid at temperatures below 77 K. The effects of surface curvature on the adsorption of nitrogen at 77 K in SWCNTs have been studied by Ohba et al (2007), both experimentally and using GCMC simulation for nanotubes with diameters distributed around 2.8 nm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…163,192 One-dimensional (1-d) and quasi-1-d phases are possible for gases adsorbed on SWNT bundles. 32,33,[193][194][195] As-prepared SWNTs are capped, making endohedral adsorption unlikely to occur to any significant extent. Many careful experimental studies of gas adsorption on closed SWNT bundles have been performed, yielding adsorption isotherms, binding energies, and isosteric heats of adsorption (q st ).…”
Section: Introductionmentioning
confidence: 99%